Winning Back Technology Disadopters: Testing a Technology Readoption Model in the Context of Mobile Internet Services. Issue 1 (2nd January 2017) - Xu, Xin; Thong, James Y.L.; Tam, Kar Yan
Abstract: We investigate how information and communication technology (ICT) service providers can win back disadopters of an earlier generation of technology when a new technology generation appears on the market. Integrating prior research on consumers' defensive bias, knowledge accessibility, diffusion of innovation, and technology adoption, we developed a model to predict disadopters' intention to readopt a technology. We postulate that the primary reason for disadoption moderates the impacts of both the drivers of readoption (perceived superiority, effort expectancy, price value of the new technology generation, and social influence) and the characteristics of prior usage experience with the disadopted earlier technology generation (duration of disadoption, tenure with the old generation, and usage intensity of the old generation) on readoption intention. We tested our technology readoption model in the context of mobile Internet services. Data were collected from 274 disadopters of an earlier generation of mobile Internet services before the advent of the third generation (3G) technology. The results supported most of our hypotheses. These findings have significant theoretical and practical implications, especially for firms interested in winning back technology disadopters. Finally, we present an agenda for further research into technology readoption.